The Effect of Promotion on the Assessment of Maternity Leave and the Welfare of Women Workers - Tenrilemba, Farahdibha; Muljono, Pudji; Hastuti, Dwi; Saleh, Amiruddin (Journal of Posthumanism, 2025)
Many workers in Indonesia are not fully aware of female workers’ rights regarding maternity leave due to a lack of clear and easily accessible information about maternity leave regulations. Some companies often fail to provide sufficient information regarding maternity leave entitlements to their workers. This study aims to analyze the influence of maternity leave promotion, female worker characteristics, social support from family and peers, and attitudes toward maternity leave policy evaluation on the welfare of female workers in garment companies in Bandung. The research employs a mixed-methods approach with a sequential explanatory design. The quantitative phase tests the research hypotheses through a survey using a structured questionnaire, while the qualitative data is collected through interviews. The findings indicate that the validity of all variables is well-established, with the following values: female worker characteristics (0.775), social support (0.952), maternity leave promotion (0.954), policy (0.962), evaluation (0.949), and welfare (0.957). Overall, these results confirm that all indicators used in this study are valid measures of their respective constructs. Hypothesis testing results reveal that: (1) maternity leave promotion, female worker characteristics, social support, and attitudes toward policies significantly influence the evaluation of maternity leave policies and the welfare of female workers; (2) maternity leave promotion, female worker characteristics, and social support significantly influence female workers’ attitudes toward maternity leave policies.